The Urgency of Implementing Asset Confiscation in Corruption and Money Laundering for Law Enforcement in Indonesia - Simatupang, Robin (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study's primary goal is to outline the role of the Indonesian National Police in combating the widespread violations of the Money Laundering Criminal Act by examining the Central Java Regional Police Department's investigations and examining the variables that affect how those investigations are carried out. Based on the study's goal and problem, this is descriptive research. Utilizing qualitative research kinds and sociological juridical research methodologies, the investigation was analyzed. According to Article 74 of the Law of Money Laundering, the research highlighted that money laundering investigations are conducted efficiently and promptly. This is achieved via the implementation of systematic work management, which is necessary to promote efficient and effective work in order to handle a case more swiftly and measurably. The purpose is to make it easier for investigators to look into riches obtained via illegal activity, which is inextricably linked to gathering evidentiary tools for the investigation of all 183 Jo 184 illegal Procedure Code and article 73 Law on Criminal Procedure. 2) Legal considerations, legal action, legal reasoning, or facilities that assist law enforcement and community members are reasons that inspire the investigator to look into illicit money laundering.